Factors Affecting the Choice of Adaptation Strategies to Climate Extremes: The Case of Smallholder farmers in Southern Zambia - Kiru Sichoongwe; Jinxia Wang (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2023)
This study assesses the adaptation of smallholder farmers to climate extremes and its contributing factors in Zambia’s southern province. The study employed primary data collected from 270 smallholder farmers, and these constituted the sample size. According to the study's findings, change crop variety was adopted by 43% of the farmers. Other strategies of adaptation that were employed include; agricultural insurance, change sow/harvest date, crop diversification and soil conservation. The findings also showed that the various strategies of adaptation (agricultural insurance, change sow/harvest date, crop diversification and soil conservation), correlated positively with age, education, distance, farming experience, ownership of a radio, an ox, a plough, and extension source. The study makes the following recommendations; (a) enhancing the education and awareness level of farmers towards climate extreme, (b) improving farmers’ access to agricultural assets (plough, oxen etc), and (c) when developing and implementing adaptation strategies, farming experience should be taken into account.